The Relationship Between Tiktok Exposure and English Vocabulary Acquisition Among English Education Students at Tadulako University - Gusti Ayu Kadek Velli Amanda; Konder Manurung; Moh. Abraham Akbar Eisenring; Afrillia Anggreni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aimed to investigate the relationship between TikTok exposure and English vocabulary acquisition among English Education students at Tadulako University. Using a quantitative correlational design, data were collected from 60 students selected through purposive sampling using an online questionnaire and analyzed using SPSS. The findings showed a mean score of 43.4 for TikTok exposure and 36.9 for vocabulary acquisition. Spearman’s Rank Correlation revealed a correlation coefficient of 0.494 with a significance value of less than 0.001, indicating a positive and statistically significant relationship between TikTok exposure and English vocabulary acquisition. These findings suggest that students with higher TikTok exposure tend to have higher levels of English vocabulary acquisition.